LEGAL PROTECTION FOR CREDITORS IN PAWN TRANSACTIONS: A CASE STUDY OF MSMEs IN THE INDONESIAN RETAIL SECTOR - Sanusi, Sanusi (SYNTIFIC, 2024)
Background. Pawn transactions have become a significant alternative financing instrument for MSMEs, especially in retail. In Indonesia, pawn transactions will increase by 15% in 2023, with MSMEs as the primary users. However, legal protection for creditors still faces challenges, especially regarding collateral execution and default risk. This study aims to analyze and evaluate the effectiveness of legal protection for creditors in pawn transactions involving MSMEs in the retail sector and to provide strategic recommendations to strengthen the existing legal framework. Research Method. This study uses a mixed-method approach, combining quantitative analysis through SEM-PLS with qualitative case studies. Findings. Pawn regulations significantly affect creditor protection (path coefficient 0.35, p <0.001), but there are still weaknesses in implementation, especially related to transparency and collateral Execution. Qualitative analysis shows that legal education and regulatory reform are urgently needed for legal protection. Conclusion. To create a more stable financial ecosystem for MSMEs in the Indonesian retail sector, the interests of creditors and debtors must be balanced through increased transparency, legal education, and simplification of collateral execution mechanisms.